The Role of Foreign Direct Investment in Economic Development: A Consideration of the Chinese Experience - Guerfi, Omar (Finance and Business Economies Review, 2022)
The study aims to highlight the importance of foreign direct investment in enhancing the country’s economic development. The work presents one of the world's leading experiences in this field, which is the Chinese experience. The purpose is to benefit from this experience and promote foreign and domestic direct investment that depends on innovation, especially in the light of the foundations and the qualifications that are available in the Arab countries, including Algeria, on the one hand, and the indicators that place them in late ranks in this field on the other hand. The study results showed that the level of creative capabilities and economic components that characterize China are great. Similarly, exploiting these components in foreign direct investment has a positive impact on fostering comprehensive economic development